(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Although quality assessment is gaining increasing attention, there is still no consensus on how to define and grade postoperative complications. This shortcoming hampers comparison of outcome data among different centers, therapies and over time. Objective: Objective of the study was to assess the Clavien classification of surgical complications of patients who underwent emergency laparotomy. Materials and Methods: The classification was tested on 40 patients who underwent emergency laparotomy in various Combined Military Hospitals (CMH) over a period of 09 years. Data recorded including demographics, clinical presentations, operating techniques, incision, post-operative complications and the duration of hospital stay. Results: Out of the total 40 patients, 28(70%) were male and 12(30%) female. Male: Female ratio was 2.33:1. A total of 29(72.50%) patients experienced postoperative complications. More than one complications occurred in 14(35%) patients. There were 13(32.50%) patients in the Clavien grade-I category, 09(22.50%) patients were classified as grade-II and grade-IIIa, 05(12.50%) patients had IIIb complications, grade-IVb and V complications occurred in 03(07.50%) patients each. The mean length of hospital stay was 15.28 days. Conclusion: This classification seems to be applicable in most parts of the world and may even be used by surgeons who are less experienced. In addition, standardization of postoperative care is essential to minimize postoperative complications. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 7-13